2009
DOI: 10.1038/ijir.2009.62
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bryonia laciniosa seeds on sexual behaviour of male rats

Abstract: Ethanolic extract of seeds of Bryonia laciniosa Linn was administered orally to groups of male albino rats at the dose levels of 50, 100, and 150 mg kg À1 body weight per day for 28 days. The changes in sexual behaviour, reproductive organ weights, histology of testis and epididymis, epididymal sperm density, and androgenic hormone levels were evaluated. The sexual behaviour parameters studied such as mount frequency, intromission frequency, mount latency, intromission latency were significantly affected. Incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 15 publications
0
33
0
Order By: Relevance
“…Testosterone is the main male gonadal hormone produced by Leydig cells in the testes in response to LH and under the control of the hypothalamic-pituitary axis [24]. A certain concentration of this hormone is necessary for the initiation and maintenance of spermatogenesis and for stimulating the growth and functioning of the prostate and seminal vesicles [25]. Moreover, it has been reported that the increase in both the sperm concentration and the weight of sexual organs is an indicator of improving male fertility [19].…”
Section: Discussionmentioning
confidence: 99%
“…Testosterone is the main male gonadal hormone produced by Leydig cells in the testes in response to LH and under the control of the hypothalamic-pituitary axis [24]. A certain concentration of this hormone is necessary for the initiation and maintenance of spermatogenesis and for stimulating the growth and functioning of the prostate and seminal vesicles [25]. Moreover, it has been reported that the increase in both the sperm concentration and the weight of sexual organs is an indicator of improving male fertility [19].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these plant materials are used for sexual problems or as aphrodisiacs (Chauhan & Dixit, 2010;Chauhan et al, 2011;Kaufman & Cannon-Smith, 2007). An aphrodisiac component is defined as any food or drug that arouses the sexual instinct, induces veneral desire and increases pleasure and performance (Yakubu et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…The ethanolic extract of seeds shows androgenic as well as improvement of sexual behaviour of rat in dose dependent manner, it also improve the histoarchitecture of testis and increase the concentration of sperm count in epididymis and also increase testosterone level (Chauhan et al, 2009(Chauhan et al, , 2010.…”
Section: Aphrodisiac Activitymentioning
confidence: 99%